Experienced and inexperienced Internet users among pre-service teachers: their use and attitudes toward the Internet - Wong, Su Luan; Ng, Siew Fung; Nawawi, Mokhtar; Tang, Sai Hong (International Forum of Educational Technology & Society, 2005)
Much has been said about the benefits of the Internet as a teaching and learning tool but to realize these benefits, teachers must be willing and able to use the Internet effectively in their teaching. Studies have also clearly shown that the likeliness of teachers using the Internet effectively and the success of Internet utilization was very much related to the users' attitudes toward the Internet (Liaw, 2002; Moon & Kim, 2001; Johnson & Hignite, 2000). This paper describes a study on pre-service teachers with differing levels of Internet experience, at one of the premier universities in Malaysia, to assess their Internet use and attitudes toward the Internet. The study is exploratory in essence and seeks to ascertain the comfort level of pre-service teachers where the Internet is concerned and hence to provide a glimpse of the future of the Internet in education within the Malaysian context.